Case study: Sowing Seeds of Sustainability: A Case Study on Singrass’s Indoor Smart Eco Farm - Shi, Jianzheng; Li, Ruiwu (Eximia, 2023)
This case study explores the innovative approach of Singrass, an indoor smart eco farm based in Singapore, in revolutionizing urban farming. Singrass specializes in cultivating 27 types of fresh, pesticide-free leafy vegetables and spices, promoting sustainable and eco-friendly farming practices in urban spaces. The indoor smart ecosystem of Singrass leverages the existing indoor conditions to purify the air from harmful pollutants and acts as a carbon sink, absorbing more carbon dioxide than it releases. By creating a controlled environment indoors, Singrass optimizes the growth of leafy vegetables, ensuring they are free from pesticides and safe for consumption. This paper discusses the benefits of such a system, including reduced environmental impact, energy efficiency, improved air quality, stress relief, cost savings, and convenience in gardening. The paper also compares Singrass’s air purification method with traditional air purification systems and discusses the energy-saving features and technologies incorporated in indoor smart ecosystems. The study concludes by highlighting the significant role of innovative solutions like Singrass in promoting sustainability and food security in growing urban settings.